Effects of Psychoeducation on People With Schizophrenia in Long-Term Care An Intervention Study - Alhadidi, Majdi; Al Hadid, Lourance Abdel Razzaq; Danaee, Mahmoud; Khatijah Lim, Abdullah *; Tang, Li Yoong (Slack Journals, 2023)
The aim of the current study was to examine the effect of a psychoeducation intervention on knowledge, insight, and internalized stigma among people with schizophrenia in a long-term care (LTC) facility in Jordan. This study was conducted based on cluster randomization using a pre- and post-test design. The intervention group (n = 66) received seven sessions about schizophrenia over a 3-week period along with usual treatment. The control group (n = 56) received usual treatment only. The psychoeducation intervention significantly improved knowledge (15.5%) and insight (22.5%) and reduced stigma (18%) among participants in the intervention group compared to the control group (2.6%, 4.7%, and 3.6%, respectively). This study shows the importance of integrating psychoeducation interventions in routine care for people with schizophrenia in LTC. [Journal of Psychosocial Nursing and Mental Health Services, 61(2), 9-18.].